ANALISIS PERAN PADA ORANG TUA DALAM PEMBENTUKAN AKHLAK ANAK MILLENIAL DI SEKOLAH MADRASAH ALIYAH ALLU KECAMATAN BANGKALA KABUPATEN JENEPONTO - Hajrah Hajrah (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2021)
The purpose of this study was to determine the role of parents in fostering children's morals and understand the supporting and inhibiting factors of parents in fostering the morals of children in the digital era (millennials) at MA Allu. The type of research in this study is qualitative and uses a field research approach. Sources of research data were taken from 10 students at Madrasah Aliyah Allu. The results of this study are firstly in fostering children's morals, and parents must play a role with their functions. First, parents must help and support each other. The role of parents is as role models, mentors and motivators. Second, the supporting factors in forming children's character are parents providing religious education, discipline in providing the necessary direction and facilities, and providing a good environment for children to become good. At the same time, the inhibiting factors are the social environment that has a bad influence on children when playing and the negative influence of digital media.